Levels, trends and differentials of teenage fertility in Nepal: assessing universal coverage of adolescence sexual and reproductive health to achieve Sustainable Development Goal 5 in 2030 - Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2015)
Introduction: Adolescence is a transition period from childhood to adulthood and is critically important especially for teenage girls as adolescent birth rate has remained high despite declining fertility in Nepal. Consequently, adolescents are more likely to drop out from the school thus losing the potential earning and leadership opportunities, which in turn, hampers their overall well-being. Thus it was included in the Millennium Development Goals and also in the Sustainable Development Goals (SDGs). Methods: The 1996, 2001, 2006 and 2011 Nepal Demographic Health and Survey (NDHS) datasets were used. Single age birth rates were derived using births histories whereas age-specific fertility rates of 15-19 years women were derived using Poisson regression. Regression-based standard errors and its confidence intervals were used to test the levels and trends statistically. Results: The adolescent birth rate was higher among 18-19 years than 15-17 years old females. Teenage fertility rate was 81 in 2011: second highest in South Asia. Urban adolescent birth rates were significantly different from rural areas and country for all the surveys. Adolescent birth rate was significantly lower than the national estimates for women with some secondary and beyond secondary levels of education. Eastern and Western Development regions had lower teenage fertility compared to other regions of Nepal. Conclusion: Nepal needs to use best practices and approaches from around the globe to systematically reduce its high teenage fertility as aspired by the Target 6, Goal 5 of the Sustainable Development Goals (SDGs) to be implemented between 2016-2030.